Notes on the identity of the species known as ‘stone-breaker’ (Phyllanthus spp., Phyllanthaceae) occurring in the Brazilian Amazon - Mendes, Jone Clebson Ribeiro; Secco, Ricardo de S. (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
The species known in the Brazilian Amazon as ‘stone breaker’ were listed based on the analysis of specific literature, and the collection of information on the specimens deposited in the Instituto Nacional de Pesquisas da Amazônia (IAN), Instituto Nacional de Pesquisas da Amazônia (INPA), Museu Paraense Emílio Goeldi (MG), and Jardim Botânico do Rio de Janeiro (RB) herbariums. Observations of these populations in their habitats were also made. According to the survey, it was found that, in the Brazilian Amazon, seven distinct species are referred to as ‘stone breaker’: Phyllanthus amarus, P. caroliniensis, P. minutulus, P. niruri, P. orbiculatus, P. stipulatus, and P. urinaria). Among these seven species, P. niruri is the least collected in this biome, since the analyzed exsiccates were incorrectly identified. This work provides diagnostic morphological characters of the species, comparative tables, identification keys, as well as information on geographic distribution and preferred habitats of the taxa.
Keywords: Taxonomic complexity; Diversity; Vernacular names; Medicinal plants